Moving through adulthood: The lived experience of Irish adults with PKU - O'Shea, Mary-Ellen; Sheehan Gilroy, Bernadette; Greaney, Anna-Marie; MacDonald, Anita (Frontiers in Psychology, 2022)
Background: This paper represents a portion of the findings from what is one of the first research studies eliciting the lived experience of adults with an early diagnosis of Phenylketonuria (PKU) living in Ireland. Ireland has one of the highest prevalence rates of PKU in Europe, however, little is known about the experience of Irish adults with PKU. Furthermore, Ireland is one of the first countries in the world to introduce neonatal screening followed by the introduction of long-term dietary therapy over fifty years ago. This study presents the first comprehensive assessment of the lived experience of Irish adults with PKU on long term dietary therapy. Methods: Narrative data was collected from eleven self-selected participants, using semi-structured interviews. The interviews were divided into five sections focused on eliciting a holistic understanding of the lived experience of adults with PKU living in Ireland. Thematic analysis was guided by Colaizzi’s Framework (1978) in conjunction with NVivo qualitative data analysis software. Findings: Findings from the original research encompassed a broad understanding of the lived experience of adults with PKU living in Ireland, including factors influencing dietary therapy and managing PHE blood levels. The themes being discussed within this article are those which appear to be least represented within current literature: living with PKU, including reproductive health, the importance of self-management and establishing routine, support networks in adulthood and concerns regarding aging with PKU. Conclusion: It was evident from the findings that a diagnosis of PKU can influence how adults with PKU may experience aging and their own mortality. These findings offer new insight into the vulnerability attached to the experience of aging with PKU and may be beneficial to advocacy groups and for future development of policy and practice.